Building youth and family resilience for better mental health: developing and testing a hybrid model of intervention in low- and middle-income countries. (January 2022) - Basu, Debasish; Nagpal, Sugandha; Pillai, Renjith R.; Mutiso, Victoria; Ndetei, David; Bhui, Kamaldeep
Summary: Resilience is a dynamic, multi-level, multi-systemic process of positive adaptation at the individual, family and community levels. Promoting resilience can be a cost-effective form of preventive and early intervention, offering significant health advantages for young people throughout their lives. Developing resiliency interventions for youth and their families in low- and middle-income countries (LMICs), particularly in the context of the ongoing pandemic, is especially important given a lack of services and trained specialists, and poor levels of public spend on mental health, alongside marked and clustered psychosocial disadvantages and adverse childhood experiences. We propose a 'hybrid' model targeting 10- to 17 year-old children and their families, and options to engage through communities, schools and the family unit. These options will enhance individual and family resilience, and possibly buffer against adversity. The adaptations respect cultural and health beliefs, take account of structural drivers of inequalities and are suitable for LMICs.